Al-Mashīkhah (Kanz al-sālikīn) : Ganjīna-yi khuṭūṭ va yādgār nāma-yi mashāhīr-i ʿilmi-yi Īrān az sāl-i 845 tā 1022 HQ - Yazdī, Najm al-Dīn Muḥammad Ḥammūʾī (Miras Maktoob, ISBN: 9789004365452., 2019)
In the history of Islam and the Islamic world, the authentication of knowledge has always been important. Thus, the Prophetic traditions are typically introduced by chains of transmission going back from the speaker, all the way to a direct witness of the Prophet's sayings or deeds. And in scholarship, too, the ijāza or licence attesting to someone's proficiency in some subject written by an established teacher was very important as well, comparable to a modern certificate or diploma. Against this background, the booklet published here is rather unique. This is because it contains study certificates and samples of the handwriting of various scholars and religious authorities, issued to five generations of scholars from one and the same family from Yazd, starting with Najm al-Dīn Muḥammad Ḥammūʾī Yazdī (d. 885/1480) and ending with Sālik al-Dīn Muḥammad Ḥammūʾī Yazdī (duwwum) (d. after 1022/1613). Most of the texts are in Arabic, while the poetry is mostly in Persian.